Android-based Augmented Reality Media in Learning Pancasila and Citizenship Education - Hannes Magdalena Hutagalung; Fazli Rachman (Jurnal Pedagogi dan Pembelajaran, 2023)
The lack of variation in the use of instructional media in the Citizenship Education learning process causes the learning process to not run optimally. The purpose of this research is to produce a product in the form of augmented reality learning media that is suitable for use in the Citizenship Education learning process. The type of research used is research and development concerning the 4D development model which consists of define, design, develop, and disseminate stages. Subjects for small-scale trials in this study used 6 students and for large-scale trials used 27 students. Product validation tests were carried out by 1 material expert and 1 media expert and 1 Pancasila and Citizenship Education teacher. Methods of data collection using observation, document study, interviews, and questionnaires. The data collection instrument is a questionnaire. The results showed that augmented reality learning media had been produced which obtained a very decent category rating from the validation of material experts with a score of 88%, media expert validation of 90%, Pancasila and Citizenship Education teachers' assessment of 91% and obtained a very interesting category from students with a score of 89%. It can be concluded that augmented reality learning media on national integration material within the framework of Bhinneka Tunggal Ika is very feasible and recommended for use in the Citizenship Education learning process. The development of augmented reality learning media provides a variety of choices for teachers to use instructional media that can create a more interactive and enjoyable Citizenship Education learning atmosphere for students.